Genetic mutation and blue rubber bleb nevus syndrome: case reports and literature review - Xing, Yueyi; Liu, Han; Liu, Hua; Ding, Xueli; Jing, Xue (Frontiers in Genetics, 2025)
Blue Rubber Bleb Nevus Syndrome (BRBNS) (OMIM %112200), or Bean syndrome, is an infrequent disorder characterized by venous malformations (VaMs) involving various organs such as the skin and gastrointestinal tract. Genetic mutations that affect the proliferation, migration, adhesion, differentiation, and survival of endothelial cells and the integrity of the extracellular matrix may be the pathogenesis of these disorders. We are supposed to investigate the cytogenetic results of BRBNS and report two sporadic cases. Two unrelated cases with BRBNS were from the Affiliated Hospital of Qingdao University and the First Affiliated Hospital of the University of South China, respectively. The data collection included information on the current age, sex, and race of the individuals, as well as their chief complaint. Clinical and family history, physical and laboratory findings, diagnostic workup, results, treatment, and complications were all documented. We are supposed to investigate the cytogenetic results of BRBNS and report two sporadic cases. We identified TEK missense mutations (c.596A>C) in both participants with BRBN. In addition, the mutation has appeared in MMP9, NOTCH3, PRSS1, PDGFRA, CCM2, TSC2, and TNFAIP6. KEGG pathway analysis showed that they participated in the PI3K-AKT signaling pathway. Our findings underscore the importance of exploring these genetic alterations in the context of BRBNS, which may have implications for developing targeted therapeutic approaches. We present two cases diagnosed with Bean syndrome, detailing their clinical features and molecular aspects.